Truncated wild-type SOD1 and FALS-linked mutant SOD1 cause neural cell death in the chick embryo spinal cord - Ghanashyam D. Ghadge; Lijun Wang; Kamal Sharma; Anna Liza Monti; Vytas Bindokas; Fred J. Stevens; Raymond P. Roos (Neurobiology of Disease, 2006)
Approximately 10% of amyotrophic lateral sclerosis (ALS) cases are familial (FALS), and ∼25% of FALS cases are caused by mutations in superoxide dismutase-1 (SOD1). Mutant (MT) SOD1 kills motor neurons because of the mutant protein's toxicity; however, the basis for toxicity is unknown. We electroporated wild-type (WT), truncated WT or MTSOD1 expression constructs into the chick embryo spinal cord. MTSOD1 and truncated WTSOD1 (as small as 36 amino acid residues in length) aggregated in the cytoplasm of cells and caused cell death. These results suggest that MTSOD1 and truncated WTSOD1 lead to neural cell death because of misfolding, and that SOD1 peptides, possibly as a result of proteolytic digestion of MTSOD, play a role in FALS pathogenesis. Electroporation of the chick embryo spinal cord is a useful system in which to investigate neurodegenerative diseases because it provides efficient delivery of genes into neural cells in situ within a living organism.